North Africa and the Mediterranean in British grand strategy planning for the opening of the second front in 1942 - Harouni, Brahim (Journal of Human Sciences, 2005)
Contrary to the thesis developed by Michael Howard in his book The Mediterranean Strategy in the Second World War, which states that Great Britain had no pre-planned strategy for the Mediterranean, this country had from the very beginning of the war, started to evolve a consistent approach in which the control of North Africa and the Mediterranean was a central priority for waging the future war in Europe. This article attempts to show how Winston Churchill, the British Prime Minister and his Chiefs of Staff had developed their war strategy for the Mediterranean andNorth Africa and how they manoeuvred with their American counterparts to make of this area the only possible option for a second front in 1942.